Prevalence and incidence of ocular trauma in North China: the Beijing Eye Study - Wang, Jin-Da; Jonas, Jost B. (Acta ophthalmologica, 2012)
Abstract. Purpose: To determine the prevalence and incidence of ocular trauma and proportion of trauma-related visual impairment in the population of Greater Beijing. Methods: The population-based Beijing Eye Study included 4439 subjects in 2001, of whom 3251 subjects returned for follow-up examination in 2006 (response rate: 73.3%). The subjects underwent a comprehensive ocular evaluation. Prospective information on ocular trauma and type of treatment was recorded with questionnaires in face-to-face interviews. Results: A history of ocular trauma was reported by 72 (1.6 ± 0.2%) subjects (age-standardized prevalence: 1.7 ± 0.01%). Prevalence of ocular trauma history was associated with male gender (p = 0.02), rural residence (p = 0.04) and alcohol consumption (p = 0.01). Trauma as underlying cause for visual impairment (best-corrected visual acuity <20/60 and ≥20/400) was found in 4 (6.6%) eyes and as underlying cause for blindness (best-corrected visual acuity <20/400) in three eyes (4.2%). In the survey of 2006, 116 (3.6 ± 0.3%) participants had a self-reported history of ocular trauma, which was associated with male gender (p = 0.002), low income (p = 0.01) and alcohol consumption (p = 0.016). The 5-year incidence of ocular trauma was 2.6 ± 0.3%, which was associated with male gender (p = 0.02), younger age (p = 0.037) and lower income (p = 0.009). Conclusions: In the adult population of Greater Beijing with an age of 40+ years, the prevalence of ocular trauma was 1.6 ± 0.2% and was associated with male gender, rural residence and alcohol consumption. The age-standardized ocular trauma prevalence of 1.7 ± 0.01% was comparable with figures from Caucasian populations. The 5-year incidence of ocular trauma of 2.6 ± 0.3% was associated with male gender, younger age and lower income.
First published: 23 August 2011
Gesehen am 26.11.2018